Anti‐interleukin‐6 antibody clazakizumab in late antibody‐mediated kidney transplant rejection: effect on cytochrome P450 drug metabolism. (8th July 2021) - Mühlbacher, Jakob; Schörgenhofer, Christian; Doberer, Konstantin; Dürr, Michael; Budde, Klemens; Eskandary, Farsad; Mayer, Katharina A.; Schranz, Sabine; Ely, Sarah; Reiter, Birgit; Chong, Edward; Adler, Scott H.; et al.
Summary: Targeting interleukin‐6 (IL‐6) is a promising strategy to counteract antibody‐mediated rejection (ABMR). In inflammatory states, IL‐6 antagonism was shown to modulate cytochrome P450 (CYP), but its impact on drug metabolism in ABMR treatment was not addressed so far. We report a sub‐study of a phase 2 trial of anti‐IL‐6 antibody clazakizumab in late ABMR (ClinicalTrials.gov, NCT03444103). Twenty kidney transplant recipients were randomized to clazakizumab versus placebo (4‐weekly doses; 12 weeks), followed by a 9‐month extension where all recipients received clazakizumab. To study CYP2C19/CYP3A4 metabolism, we administered pantoprazole (20 mg intravenously) at prespecified time points. Dose‐adjusted C0 levels (C0 /D ratio) of tacrolimus ( n = 13) and cyclosporin A (CyA, n = 6) were monitored at 4‐weekly intervals. IL‐6 and C‐reactive protein were not elevated at baseline, the latter was then suppressed to undetectable levels under clazakizumab. IL‐6 blockade had no clinically meaningful impact on pantoprazole pharmacokinetics (area under the curve; baseline versus week 52: 3.16 [2.21–7.84] versus 4.22 [1.99–8.18] μg/ml*h, P = 0.36) or calcineurin inhibitor C0 /D ratios (tacrolimus: 1.49 [1.17–3.20] versus 1.37 [0.98–2.42] ng/ml/mg, P = 0.21; CyA: 0.69 [0.57–0.85] versus 1.08 [0.52–1.38] ng/ml/mg, P = 0.47). We conclude that IL‐6 blockade in ABMR – in absence of systemic inflammation – may have no meaningful effect on CYP metabolism. Abstract : In inflammatory disease states, interleukin‐6 antagonism was shown to interfere with CYP450 metabolism. In this phase 2 pilot trial of anti‐interleukin‐6 antibody clazakizumab in late antibody‐mediated rejection ‐ in absence of systemic inflammation ‐ we found no significant effect of treatment on the pharmacokinetics of CYP substrate pantoprazole and dose‐adjusted calcineurin inhibitor levels. Abbreviations: ABMR, antibody‐mediated rejection; CYP, cytochrome P450; DSA, donor‐specific antibodies; eGFR, estimated glomerular filtration rate; EP, endpoint; IL‐6, interleukin‐6, PK, pharmacokinetics.